Acquisition of Literacy Skills using Mobile Handheld Devices and Science Education Students' Academic Performance in Universities in Akwa Ibom State, Nigeria - Itighise, Atim Edet; Akpan, Iniobong Fred (NIU Journal of Humanities, 2022)
This survey study examined acquisition of literacy skills through the use of handheld devices and academic performance among Science Education students in Universities in Akwa Ibom State, Nigeria. The population of this study comprised of level 200 Science Education students which was 1080 (440 male and640 female) in Universities in Akwa Ibom State. The sample consisted of one hundred and twenty (120) Science Education students drawn from two universities in the State. Two instruments used were: Acquisition of Literacy Skills using Handheld Devices Questionnaire, ALSHDQ (a =.70) and Computed Result Sheet (CRS).  Three research questions guided the study.  The data were analyzed using mean, frequency count, percentage, t-test and Pearson Product Moment Correlation (PPMC).  The results showed that the level of acquisition of literacy skills through handheld devices among Science Education students was high (weighted mean, x =3.07); Male and female Science Education students had similar performance mean scores (t = .905)and Science Education students acquisition of literacy skills through Handheld Devices was positively related to their academic performance (r = .555).  It was concluded that the level of literacy skills acquisition through handheld devices among Science Education students was high, and that there was no difference in the performance means scores of male and female Science Education students exposed to handheld devices in acquisition of literacy skills. Keywords: Acquisition, literacy skills, handheld devices, Academic performance, and Science Education Students, Universities.